The role of von Willebrand factor in determining the risk of ischemic stroke in Hawler city: a case-control study - Hameed, Sazgar Anwar; Ahmed, Salar Adnan (Zanco Journal of Medical Sciences (ZJMS), 2018)
Background and objective: Ischemic stroke is classically characterized as a neurological deficit attributed to an acute focal injury of the central nervous system by a vascular cause, it occurs as a result of obstruction by a blood clot (thrombus) or plugs within a blood vessel supplying blood to the brain. In this study, we investigated the association of von Willebrand factor-antigen and serum lipids with ischemic stroke. Methods: The following retrospective study was conducted on 138 participants; 88 patients with ischemic stroke and 50 healthy controls. Results: In crude analyses, Plasma von Willebrand factor antigen, fasting serum Total cholesterol, Triglycerides and LDL-C were significantly higher in patients with ischemic stroke than in controls (P <0.001, P <0.001, P = 0.003, P <0.001, respectively), while the difference in the level of serum HDL-C between patients with ischemic stroke and control was significantly lower (P = 0.023). Conclusion: These data suggest that von Willebrand factor, total cholesterol, triglycerides, LDL-C and HDL-C gives some contribution to stroke risk even in the elderly and that von Willebrand factor antigen and lipid profile assessment must be taken into account in estimating the individual risks of stroke.